Knowledge and perception of spiritual care among nursing students in International Islamic University Malaysia, Kuantan, Pahang - Mahat, Nur Ain (UniKL Royal College of Medicine Perak, 2023)
The incorporation of spiritual care into holistic patient care has been widely acknowledged as essential. However, nurses continue to face challenges in effectively addressing the requirements for comprehensive spiritual intervention, with one notable barrier being the insufficient education and training in spiritual care. This component holds significance in equipping students with the capacity to deliver spiritual care to patients and thereby strengthening the influence of spirituality on individual’s overall quality of life and their physical and mental well-being. Hence, this study aimed to assess the knowledge and perception of spiritual care among nursing students at the International Islamic University Malaysia, Pahang, Malaysia. This cross-sectional study was carried out among 95 nursing students in their second to fourth years of study, selected through convenience sampling. Frequency tables were employed to describe the categorical data. Independent t-test, one-way ANOVA and Pearson correlation were used to examine the association between sociodemographic factors with knowledge and perception on spiritual care. P value<0.05 was considered statistically significant. The results indicated that the participants had a mean knowledge score of 10.64, SD=1.44 (min=5, max=13) and a mean perception score of 66.03, SD=8.06 (min=47, max=85). However, there were no significant association between the sociodemographic factors and the knowledge (p>0.05). Also, there were no significant association between the sociodemographic factors and the perception (p>0.05), except for CGPA, which showed a significant association, at p=0.018. These results suggest that factors beyond sociodemographic factors play a role in shaping nursing students' knowledge and perception on spiritual care. Further research is needed to identify these factors and to understand their impact on spiritual care in nursing education and practice.